Analisis Dampak Ekosistem Lingkungan terhadap Kebijakan Pembangunan Ibu Kota Nusantara (IKN) di Kalimantan Timur - Najwa Adhwa Ramadhani; Zahra Hanifah Salma; Fandan Prima Jaya Zai; Ridwan Ridwan (Public Service and Governance Journal, 2025)
The policy of developing Nusantara Capital City was made by the government to reduce inequality between islands in Indonesia. East Kalimantan, which has tropical rainforests, was chosen as the destination for the development of Nusantara Capital City. The selection of East Kalimantan as the main development destination certainly has an impact on the environmental ecosystem in the forest area in the development area of Nusantara Capital City. This research analyzes the impact and government efforts in dealing with environmental ecosystem problems in the development area of Ibu Kota Nusantara. The method used in this research is descriptive qualitative research method which is expected to help in the process of problem identification. This research sees that the development of Nusantara Capital City can have the potential for deforestation, environmental damage, water pollution to degradation of soil quality. The government provides efforts by issuing Law Number 3 of 2022 concerning the development of the Nusantara Capital City which focuses on environmental protection and management by using the Forest City concept, reforesting and restoring ecosystems and conducting Environmental Impact Analysis (AMDAL) to realize the development of the Nusantara Capital City with environmental ecosystem sustainability.